Friction force microscopy of tribochemistry and interfacial ageing for the SiOx/Si/Au system - Petzold, Christiane; Koch, Marcus; Bennewitz, Roland (Beilstein Journal of Nanotechnology, 2018)
Friction force microscopy was performed with oxidized or gold-coated silicon tips sliding on Au(111) or oxidized Si(100) surfaces in ultrahigh vacuum. We measured very low friction forces compared to adhesion forces and found a modulation of lateral forces reflecting the atomic structure of the surfaces. Holding the force-microscopy tip stationary for some time did not lead to an increase in static friction, i.e., no contact ageing was observed for these pairs of tip and surface. Passivating layers from tip or surface were removed in order to allow for contact ageing through the development of chemical bonds in the static contact. After removal of the passivating layers, tribochemical reactions resulted in strong friction forces and tip wear. Friction, wear, and the re-passivation by oxides are discussed based on results for the temporal development of friction forces, on images of the scanned area after friction force microscopy experiments, and on electron microscopy of the tips.
Keywords: contact ageing; friction; nanotribology; tribochemistry; wear